Invasive Dermatophytosis in HIV/AIDS Patient by Zoophilic Trichophyton verrucosum - Wilda - Mahdani (Jurnal Kedokteran Syiah Kuala, 2021)
Invasive dermatophytosis is a dermatophyte infection characterized by fungal invasion into deeper skin tissue including the dermis and subcutaneous areas. Herein, a man who was an HIV/AIDS sufferer was reported to develop an unusually invasive dermatophytosis in the form of nodules and ulceration. His CD4+ cells count was 88 cells/µl with a percentage of 1.87%. Self-medication with topical antibiotics did not respond. Microbiological examination was carried out including direct potassium hydroxide preparation and fungal culture. The etiologic diagnosis of invasive dermatophytosis by Trichophyton verrucosum  was established. This is one of the zoophilic fungus that causes ringworm in cattle. It was suspected that the patient was inoculated due to contact with fomites containing fungi while working as a construction worker. Dermatophytes can cause atypical infections with a completely unexpected appearance in immunocompromised patients. The diagnosis is largely determined by a high level of clinical suspicion followed by microbiological examination.